CORRUPTION AS A POSSIBLE PREPARATION FOR COMMITTING OTHER CRIMINAL OFFENCES - Бантишев, Олександр Федорович; Романюк, Богдан Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: this article examines the issues of responsibility for corruption crimes and their place in the system of the Special part of the Criminal Code of Ukraine. In their study, the authors pay special attention to the fact that completed corruption offences may represent a stage for the preparation of other, perhaps more serious crimes. In particular, it may even be a preparation for such crimes as the attempt on the life of a state or public figure (article 112 of the Criminal Code), sabotage (article 113 of the Criminal Code), premeditated murder (article 115 of the Criminal Code) and other crimes against life and health. But this, as the analysis of legal literature shows, has not drawn due attention of scientists. Research methods: identification of a range of provisions of criminal law, the commission of which may precede acts of corruption; systematization of a number of shortcomings in the legal regulation of corruption crimes; determination of their place in the system of active operations as a preparation for the commission of other crimes. Results: the ways of further improvement of standards of legal regulation of the corruption crimes were determined. It was proposed to add to the list a number crimes, the purpose of which is obtaining illegal benefits. Discussion: problems of the criminal law, regulating the preparations for crimes and corruption matters.